Analisa Kualitas Permukaan Akhir Proses Pemotongan menggunakan Material Komposit dengan Serat Kaca dan Komposit dengan Serat Buah Biduri (Calotropis Gigantea) - Herman Herman; Samsul Rizal; Husni Husni (Jurnal Teknik Mesin Unsyiah, 2016)
This research study drilling quality for polyester composites with glass fiber reinforcement and polyester composite with fiber reinforcement Biduri fruit due to the influence of cutting parameters. The test is performed with the variation of machining process parameters varying the diameter of the cutting tool 5 mm, 10 mm, 14 mm, and a cutting speed of 30 m/min, 60 m/min and 90 m/min which feeds the parameters fixed. The test material used is a composite material with glass fiber reinforcement and composite with natural fiber amplifier with a size of 150 mm x 50 mm x 20 mm. The process of making composites made using hand lay-up method. Test results greater tool shows, the better the quality of the resulting hole. Due to the use of a cutting tool diameter of 5 mm would result in a continuous rage so that it will stick to the cutting tool and can interfere with the cutting tool. Cutting speed, the cutting results, the greater the cutting speed, the better the results are also cutting. Because the higher the cutting speed, the resulting fury will be more and continuous so as not to interfere with the process of cutting.